Strategi Penyelesaian Kredit Bermasalah pada Bank Perekonomian Rakyat (BPR) - Evi Kurniasih; Prayitno Prayitno (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze strategies for resolving non-performing loans at Rural Banks (Bank Perekonomian Rakyat/BPR) and to identify the factors causing problem loans. This research employs a qualitative approach with a descriptive research design using a case study at a selected BPR. Data were collected through interviews, observations, and documentation related to credit management processes and the handling of non-performing loans. The results show that the Non-Performing Loan (NPL) ratio at the BPR reached 7.86%, which exceeds the regulatory threshold of 5%. The high NPL ratio is influenced by several factors, including poor debtor character, declining business performance of debtors, weak credit analysis, and ineffective credit monitoring after loan disbursement. To address these issues, the bank implements several strategies to resolve non-performing loans, including persuasive approaches and credit restructuring. The forms of restructuring applied include loan rescheduling, extension of loan maturity, reduction of interest rates, and reduction of outstanding interest. The findings indicate that credit restructuring can assist debtors in gradually fulfilling their loan repayment obligations. Therefore, the implementation of appropriate strategies for resolving non-performing loans can help reduce the NPL ratio and maintain the stability and financial health of banking institutions.